2020
DOI: 10.1016/j.jtho.2019.09.221
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm to Differentiate Between Multiple Primary Lung Cancers and Intrapulmonary Metastasis in Multiple Lung Cancers With Multiple Pulmonary Sites of Involvement

Abstract: Introduction: Differentiating between multiple primary lung cancer (MPLC) and intrapulmonary metastasis (IPM) is critical for developing a therapeutic strategy to treat multiple lung cancers with multiple pulmonary sites of involvement.Methods: We retrospectively included 252 lesions (126 pairs) from 126 patients with surgically resected multiple lung adenocarcinomas. Each pair was classified as MPLC or IPM based on histopathologic findings as the reference standard. A novel algorithm was established with four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…Imaging test can provide unique evidence for MPLC and IPM distinguishment. A recent study established the algorithm for distinguishing MPLC from IPM by combining characteristics of lesions from CT/PET imaging and achieved good diagnostic efficacy ( 24 ). Thirdly, the criteria established in this study were based on the 605-gene panel.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging test can provide unique evidence for MPLC and IPM distinguishment. A recent study established the algorithm for distinguishing MPLC from IPM by combining characteristics of lesions from CT/PET imaging and achieved good diagnostic efficacy ( 24 ). Thirdly, the criteria established in this study were based on the 605-gene panel.…”
Section: Discussionmentioning
confidence: 99%
“…Application of the algorithm based on comprehensive information on clinical and imaging variables can also allow differentiation between MPLCs and IPMs. When both of two suspected malignant lesions appear as solid predominant lesions without spiculation or air‐bronchograms on CT, IPM should be considered 14,24 . Goto et al 25 showed that LC mutation analysis by targeted deep sequencing is useful for distinction of the clonality of individual pulmonary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria based on tumor locations and pathological findings used to define MPLCs were initially published in 1975 [36] . Additionally, a novel algorithm to differentiate between MPLCs and intrapulmonary metastasis using clinical and imaging variables has been reported [38] . The algorithm showed combinations of lesion types on CT, and the presence of air-bronchogram and spiculation were the most accurate determinants for differentiation between MPLC and intrapulmonary metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…We diagnosed MPLC based on the methods described in previous studies [36] , [37] , [38] . MPLC was diagnosed if (1) paired nodules were located in different segments, lobes, or lungs; (2) either of the paired nodules was adenocarcinoma in situ (AIS) or minimally invasive adenocarcinoma (MIA); (3) the histopathologic patterns, including subtypes, were different between paired nodules; (4) nodal or systemic metastases were absent; or (5) CT imaging showed the presence of an air-bronchogram or speculation in paired nodules.…”
Section: Methodsmentioning
confidence: 99%